QOL-44. ASSESSMENT OF NEUROCOGNITIVE FUNCTION AND MRI PARAMETERS IN LONG-TERM SURVIVORS WITH POSTERIOR FOSSA TUMORS: A COMPARISON BETWEEN MEDULLOBLASTOMAS TREATED BY REDUCED-DOSE CRANIOSPINAL IRRADIATION AND OTHER TUMORS. (4th December 2020) - Kagawa, Naoki; Miyamura, Takako; Hirayama, Ryuichi; Yokota, Chisato; Nakagawa, Tomoyoshi; Kijima, Noriyuki; Kinoshita, Manabu; Hashii, Yoshiko; Okada, Keiko; Hara, Jyunichi; Kishima, Haruhiko
Abstract: BACKGROUND: Children with medulloblastoma cannot avoid chemoradiotherapy including craniospinal radiation, although prognosis of medulloblastoma has improved and previous studies have reported a significant risk of intellectual disturbance by these treatments. We retrospectively analysed neurocognitive functions, clinical MRI parameters of patients with posterior fossa tumors, especially medulloblastomas. MATERIALS AND METHODS: Twenty-two patients (12 medulloblastomas, 5 ependymomas, 5 astrocytomas) treated in our institution were enrolled in this study. Mean age was 7.8 years and 6.5 years, percentage of hydrocephalus at onset was 66.7% and 60%, respectively in medulloblastoma group and in other tumor group (ependymoma and astrocytoma). Postoperative chemoradiotherapy including reduced-dose craniospinal irradiation (18Gy) was done for medulloblastoma group and local radiation or operation only was done for other group. Version 3 or 4 of Wechsler Intelligent Scale for Children (WISC) was used by neurocognitive function analysis. Ventricular size, white matter volume and other parameters were also was estimated based on MRI. Follow-up duration was 6–17 years (mean: 10.5 years). RESULTS: Evaluations of neurocognitive functions based on WISC pointed out lower performance IQ than verbal IQ in long term survivor of both group, especially working memory (P=0.05). Both hydrocephalus and cranial nerve complications was influenced lower scores of WISC, but age at onset did not influence WISC scores. Comparison between both group showed there was no significant difference about cognitive function and white matter volume.